An augmented reality system to enhance facial expressions recognision in autistic children - Bahzad Ahmad, Hawar (Journal of Advanced Computer Science & Technology, 2019)
In the past decade, Augmented Reality (AR) has been applied in several professional practice areas, including but not limited to autism therapy. AR supplies virtual information to the visual perceptions of users, giving the user new tools to ensure that knowledge for many processes and in many environments are comprehended efficiently. Usually, AR applications depend on virtual reality headset (VR-box) to overlay virtual objects and text on the surrounding environment of the user.People with autism spectrum condition (ASC) especially children are often found lacking in social interaction, including facial expres-sion and understanding of other minds which make social communication more difficult for them. This paper aims to use AR system to assist children with (ASC) in better understanding facial expressions by overlaying suggested 3d objects over the physical environment. Results of AR treatment found higher engagement and more effective compare to a non-AR system.This paper utilizes Vuforia to create an AR environment for the treatment of children with ASC. Vuforia is a software development kit that provides AR capabilities to smartphone devices.